Generalized Blistering in Infancy: A Rare Case Report on Bullous Mastocytosis - Haldar, Aditi; Supekar, Bhagyashree; Mande, Vishwajeet; Mukhi, Jayesh (Nepal Journal of Dermatology, Venereology & Leprology, 2026)
Mastocytosis is a rare myeloid neoplasm characterized by abnormal proliferation of mast cells, associated with c-KIT mutations. The disease is most frequently observed in childhood, with clinical presentations ranging from solitary mastocytoma to diffuse cutaneous involvement. Bullous mastocytosis is an uncommon variant of diffuse cutaneous mastocytosis, characterized by dermoepidermal separation due to mast cell degranulation, and may clinically resemble other vesiculobullous disorders. We report the case of a 12-month-old male presenting with generalized pruriginous tense vesicles and bullae, evolving over three months with intermittent exacerbations. Histopathology revealed subepidermal blistering with a dense mast cell infiltrate, confirmed by CD117 and tryptase positivity on immunohistochemistry, establishing the diagnosis of bullous mastocytosis. The child was successfully managed with oral corticosteroids, antihistamines, topical corticosteroids, and supportive therapy, with resolution of lesions within two weeks. This case underscores the importance of considering bullous mastocytosis in the differential diagnosis of infantile vesiculobullous disorders, as timely diagnosis and appropriate management can prevent morbidity.